Analisis Insentif Finansial dan Insentif Non Finansial Terhadap Loyalitas Kerja Karyawan (Studi Pada PT. Anta Utama Kediri) - A. Fikry Azizan; Deby Santyo Rusandy; Nisa Mutiara (Universitas Islam Kadiri, 2023)
PT Anta Utama is a ticket sales service company with experience in the fields of: Transportation, ticketing, travel documents, haj/umroh, and tourism tours. The purpose of this study is to explain whether incentives can increase employee loyalty, organizations are required to pay more attention to financial factors that affect them such as incentives and non-employee incentives. This research method is to use quantitative research and conducted at PT Anta Utama Kediri. The population in this study are all employees at PT. Anta Utama has 50 employees. The results in this study are that giving incentives is one of the company's ways or efforts to increase employee loyalty. The results of the study show that incentives and non-financial incentives simultaneously affect employee loyalty at PT Anta Utama Kediri Financial. Thus, the provision of incentives to employees shows that partially financial incentives affect employee loyalty at PT Anta Utama Kediri.